Contraceptive use, prevalence and predictors of pregnancy planning among female sex workers in Uganda: a cross sectional study - Justine Nnakate Bukenya; Rhoda K. Wanyenze; Geraldine Barrett; Jennifer Hall; Fredrick Makumbi; David Guwatudde (BMC, 2019)
Abstract Background Unintended pregnancies are associated with negative consequences to both mother and baby. Female Sex Workers (FSWs) are at high risk of unintended/unplanned pregnancies. However, prevalence of pregnancy planning and its predictors among FSWs has not been comprehensively investigated. This study was designed to determine contraceptive use, the prevalence, and predictors of pregnancy planning among FSWs in Uganda. Methods In this cross-sectional study, 819 FSWs attending most at risk populations initiative (MARPI) clinics were recruited using systematic sampling and interviewed with a pretested questionnaire that included collection of data on pregnancy intention using the London Measure of Unplanned Pregnancy (LMUP). Data were analysed using STATA version 14.0. Multinomial logistic regression model was used to identify predictors of pregnancy planning, Results Of the 819 study participants, only 90 (11.0%) had planned pregnancies. Overall, 462 (56.4%) were hazardous alcohol users and 335 (40.9%) abused drugs; 172 (21.0%) had been raped in the last 2 years and 70 (40.7%) of these accessed emergency contraception post-rape. Dual contraception use (condom and other modern method) was 58.0%. Having a non-emotional partner as a man who impregnated the FSW compared to emotional partner was significantly associated with less planned relative to unplanned pregnancy, (aRR = 0.15 95%Cl =0.08, 0.30), so was lack of reported social support compared to support from friends, (aRR = 0.44; 95% CI = 0.22-0.87), keeping all factors constant in the model. Being raped (aRR = 0.51; 95% CI = 0.31-0.84) or abuse of substances (aRR = 0.65; 95% CI = 0.45-0.93) were significantly associated with lower ambivalence relative to unplanned pregnancy but not with planned relative to unplanned pregnancy. Conclusion Compared to women in the general population, pregnancy planning was low among FSWs amidst modest use of dual contraceptive. There is an urgent need to promote dual contraception among FSWs to prevent unplanned pregnancies especially with non-emotional partners, drug users, and post-rape.